Improving The Quality of Solid Organic Fertilizer using Decomposer - Aryanto, Arie; Zikriyani, Hikmah; Gerungan, Raflen Ari; Hamdani, Fauzan; Mustaking; Insani Alifiyah, Na’ilah (Universitas Cokroaminoto Palopo, 2024)
The utilization of cow manure can reduce environmental pollution around livestock farms. One way to utilize cow manure is by turning it into solid organic fertilizer. The quality of solid organic fertilizer is determined by various factors, including the raw materials, fermentation methods, and composting time. The aim of this study is to improve the quality of solid organic fertilizer using a decomposer. The production of solid organic fertilizer in this study was carried out in two ways: first, by turning the cow manure every 10 days for 40 days (A), and second, using a decomposer with ratio of 1 Liter/3 tons to the cow manure and then turning it every 10 days for 40 days (B). The results showed an increase in C-organic content by 9.56%, nitrogen by 42.02% , phosphate by 19.00% and potassium by 6.56%. This indicates that the addition of a decomposer in the composting process can improve the quality of solid organic fertilizer.